A Tris(bipyridine)ruthenium(II)–β‐Cyclodextrin Derivative: Synthesis, Luminescent Properties, and Application in Electrochemiluminescence DNA Sensors. Issue 8 (11th June 2013) - Chen, Hong; Wang, Xiuhua; Qi, Yantao; Zheng, Shanshan; Chen, Qiong; He, Pingang; Zhang, Fan; Yang, Fan; Tang, Jie; Fang, Yuzhi
<x xml:space="preserve">Abstract</x> Miraculous metallocyclodextrin: A new polynuclear metallocyclodextrin complex, tris(bpyRu)–β‐CD (bpy=bipyridine), was successfully synthesized. This complex possesses molecular‐recognition functions and unique luminescent properties. A tris(bpyRu)–β‐CD film was fabricated and utilized in a electrochemiluminescence (ECL) DNA sensor based on its molecular‐recognition and luminescence characteristics (see scheme).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>